The Unfolded Protein Response and Autophagy as Drug Targets in Neuropsychiatric Disorders - Srinivasan, Vignesh; Korhonen, Laura; Lindholm, Dan (Frontiers in Cellular Neuroscience, 2020)
Neurons are polarized in structure with a cytoplasmic compartment extending into dendrites and a long axon that terminates at the synapse. The high level of compartmentalization imposes specific challenges for protein quality control in neurons making them vulnerable to disturbances that may lead to neurological dysfunctions including neuropsychiatric diseases. Synapse and dendrites undergo structural modulations regulated by neuronal activity involve key proteins requiring a strict control of their turnover rates and degradation pathways. Recent advances in study of the unfolded protein response (UPR) and autophagy processes have brought novel insights into the specific roles of these processes in neuronal physiology and synaptic signaling. In this review, we highlight recent data and concepts about UPR and autophagy in neuropsychiatric disorders and synaptic plasticity including a brief outline of possible therapeutic approaches to influence UPR and autophagy signaling in these diseases.